ANALISIS FAKTOR YANG MEMPENGARUHI KEGAGALAN AUDITOR EKSTERNAL DALAM MENDETEKSI INDIKASI KECURANGAN KEUANGAN - Habi Bullah; Robiatul Auliyah (Master of Accounting Universitas Trunojoyo Madura, 2015)
The purpose of this research is to examine and analyze the influence of audit complexity, scope of audit, and risk assessment of failure to detect indications of fraud. This research is conducted in the Finance Examiner Organization of Republic of Indonesia represented East Java Province (BPK RI). The samples of this research are 54 respondents. The collecting samples technique which used in this research is purposive sampling. The collecting data use questionnaire by a large number of answers are based on a 5-point likert scale.The result of this research reveals that the audit complexity do not significantly of failure to detect indications of fraud. Nevertheless, scope of audit and risk assessment influence significantly of failure to detect indications of fraud.